Do patients with blunt thoracic aortic injury present to hospital with unstable vital signs? A systematic review and meta-analysis. Issue 4 (9th February 2018) - Bade-Boon, Jordan; Mathew, Joseph K; Fitzgerald, Mark C; Mitra, Biswadev
Abstract : Background: Blunt thoracic aortic injury (BTAI) is an uncommon diagnosis, usually developing as a consequence of high-impact acceleration–deceleration mechanisms. Timely diagnosis may enable early resuscitation and reduction of shear forces, essential to prevent worsening of the injury prior to definitive management. Death is commonly due to haemorrhagic shock, but clinical features may be absent until sudden and massive haemorrhage. Objectives: The aim of this systematic review was to determine the proportion of patients with BTAI who present with unstable vital signs. Methods: Manuscripts were identified through a search of MEDLINE, EMBASE and the Cochrane Library databases, focusing on subject headings and keywords related to the aorta and trauma. Mechanisms of injury, haemodynamic status and mortality from the included manuscripts were reviewed. Meta-analysis of presenting haemodynamic status among a select group of similar papers was conducted. Results: Nineteen studies were included, with five selected for meta-analysis. Most reported cases of BTAI (80.0%–100%) were caused by road traffic incidents, with mortality consistently higher among initially unstable patients. There was statistically significant heterogeneity among the included studies (P<0.01). The pooled proportion of patients with haemodynamic instability in the setting of BTAI was 48.8% (95% CI 8.3 to 89.4). Conclusions: Normal vital signs do not rule out aortic injury. A high degree of clinical suspicion and liberal use of imaging is necessary to prevent missed or delayed diagnoses.